Գրիգոր Երևանցի՝ ԺԷ. դարի երկրորդ կեսի մի արդյունաշատ գրիչ - Հարությունյան, Խաչիկ (Մատենադարան)
Our study of the scriptoria in Yerevan and its environments has revealed the name of a prolific scribe form the second half of the 17th century, who has copied about three dozens of manuscripts in Yerevan, Noragavit‘ and Etchmiadzin. In his colophons, he always signed as Grigor Yerevants‘i, and thanks to these scribal notes and colophons, we have been able to find out some information about the scribe and his family as well, which has helped us in the study of several manuscripts. On the basis of the paleographic features of the manuscripts and by a linguistic and stylistic analysis of their colophons, we have identified 29 manuscripts completely or partially copied by scribe Grigor. Among his commissioners were representatives of various social groups and clergy, including two Armenian Catholicoi, Eghiazar I Aynt‘apts‘i (1682–1691) and Nahapet I Edesats‘i (1691–1705). A list of the scribe’s manuscripts is presented in a separate table at the end of this article (see Table 1). Most of the manuscripts (20) are kept at Matenadaran, four are in the library of the Armenian Patriarchate of Jerusalem, two are in the collection of the Mekhitarist Fathers in Venice, one is in the National Library of France and one, at the Institute of Oriental Manuscripts in St. Petersburg. The current location of one manuscript is unknown (it was registered in the catalogue of the Armash monastery). Изучение скриптория Еревана и его окрестностей выявило имя плодовитого писца второй половины 17-го века, скопировавшего около трех десятков рукописей в Ереване, Норагавите и Эчмиадзине. В своих колофонах он всегда подписывался как Григор Ереванци. В этих записях и колофонах содержатся некоторые данные о писце и его семье, что помогло в изучении нескольких рукописей. На основе палеографических особенностей рукописей и лингвостилистического анализа их колофонов было определено 29 рукописей, полностью или частично скопированных писцом Григором. В число его заказчиков входили представители различных социальных групп и духовенства, в том числе два армянских католикоса – Егиазар I Айнтапци (1682-1691) и Наапет I Эдесаци (1691-1705). Список рукописей писца представлен отдельной таблицей в конце статьи (см. Таблицу 1). Подавляющее большинство хранится в ереванском Матенадаране (20 рукописей), 4 рукописи находятся в Армянском Патриархате Иерусалима, две другие – в собрании отцов Мхатаристов в Венеции, другие – в Национальной библиотеке Франции (1 рук.), в Институте восточных рукописей Санкт-Петербурга (1 рук.). Настоящее местонахождение одной рукописи неизвестно (она была зарегистрирована в каталоге рукописей монастыря Армаш).
Keywords: Բանասիրություն